Tres estatuillas antropomorfas de tipo capacocha en el Complejo Arqueológico de Cajamarquilla: sobre la representación de lo masculino y femenino en el mundo inca - Nautré, Caroline; Gutiérrez, Andrea (Pontificia Universidad Católica del Perú, 2025)
The discovery of three Inca statuettes usually associated with high-altitude mountain contexts at the Cajamarquillla Archaeological Complex, an urban centre on the central Peruvian coast, has questioned our approaches to and our knowledge of the social and political dynamics of this Late Horizon (1470-1532 A.D.) monumental site. Similar finds made in the last decades as well as the accounts found in the Spanish chronicles, suggest that we must reconsider whether these are unmistakable indicators of a capacocha, the most significand and solemn sacrifice in the Inca State. The raw materials used in their manufacture, along with their textile and metal associations allow us to go beyond and explore them as materialised manifestations of a key concept in the Andean worldview: male and female dualism.

Comúnmente asociadas a contextos ubicados en las altas montañas, el hallazgo de tres estatuillas inca en el Complejo Arqueológico de Cajamarquilla, un centro urbano localizado en la costa central peruana, cuestiona nuestras aproximaciones y conocimientos sobre las dinámicas sociales y políticas en este sitio monumental durante el Horizonte Tardío (1470-1532 d.C.). Descubrimientos similares realizados en las últimas décadas, así como relatos en crónicas españolas, nos invitan a repensar si se tratan de indicadores inequívocos de la ejecución de una capacocha, el sacrificio más importante y solemne del Estado inca. Asimismo, su materia prima y asociaciones textiles y metálicas nos permiten profundizar y explorarlas como expresiones materializadas de un concepto clave de la cosmovisión andina: la dualidad masculina y femenina.
Three capacocha-type anthropomorphic statuettes from the Cajamarquilla Archaeological Complex: on the representation of male and female in the Inca world
Keywords: Cajamarquilla; Rimac River Valley; Inca statuettes; Spondylus; Capacocha; Cajamarquilla; Valle del Rímac; Estatuillas incas; Spondylus; Capacocha; https://purl.org/pe-repo/ocde/ford#6.01.02